Editorial: System-Integrated Intelligence – New Challenges for Product and Production Engineering. (2016) - Trächtler, Ansgar; Denkena, Berend; Thoben, Klaus-Dieter
Abstract: The editorial introduces the SysInt conference series and the motivation behind it. It describes the structures and content as well as the scientific and technological background to the SysInt 2016 event held in Paderborn from June 13 th – 15 th, 2016, and provides an outline of the organizing institutions, detailing their individual perspectives on the general topic of system-integrated intelligence.